Application of professional standards for training in methods and technologies of software engineering at the higher education institutions - A. S. Minzov; O. I. Melnikova (Открытое образование (Москва), 2018)
The research is devoted to the analysis of professional standards in the course “information technologies”, its interaction and correlation with federal state educational standards of higher education. The complexities are considered, arising at application of professional standards in the higher education, appeared mainly at the assessment of professional graduate level. The present system of the higher education uses the concept “professional competence”. A unit of measure of results of educational activity in professional standards is mastering the generalized labor function of a certain qualification. Thus, it is complex enough to compare evaluations of educational and professional standards. Nevertheless, these different approaches must be combined. Search of solutions of this problem remains relevant. In the paper, special attention is given to training in the field of software engineering. This training direction emerged in Russia from recommendations of the standard of Computing Curricula: Software Engineering. It is supposed that graduates of this direction will be engaged in the future in development and support of difficult program systems, and therefore during educational process they have to receive broad basis of knowledge and skills to be able to develop software, create projects of development of a software product, as well as program documentation; manage the processes of programs’ life cycle, work in groups and manage team of performers in the process of production of software products. In accordance with recommendations of National Agency of Development of Qualification «Programmer», «The specialist in testing in the field of IT», «Software architect» are the professions to which one can train in time of a bachelor degree of «Software engineering». In this paper, the generalized labor and labor functions of these professional standards are analyzed and their general requirements are selected. In the article, the possibility of training in some generalized skills of these professional standards of students of the Program Engineering direction, since the first course is shown. In particular, relevant form of education in the form of project work is considered. The majority of the methodologies described at present was devoted to training of project work to their application at senior courses.The idea of a possibility to organize the project work in the form of the group team at the first year to study programming is put forward in this research (discipline “programming in high-level languages”). The main requirements at the organization of this process: the created software product must be complex enough because it must be separated into separate parts for participants of the project. Further, participants must try (in some or other volume) different roles in this project: development of architecture, creation of a code and testing of the project. Finally, everyone should develop a text document in its own part. Involvement of students in project work (especially, IT) is extremely relevant skill because in modern life few of the programmers work alone. Certainly, at the first year, it will be only the beginning of the movement in this direction, but it is extremely important and useful for the future deeper understanding of the software development process.